Vulnerabilidade socioambiental na gestão de efluentes urbanos: uma análise multidimensional - Bernardini, Camila Santiago Martins (2022)
The management of urban effluents belongs to a web of multiple socio-environmental aspects. In addition to the marked deficit in sewage coverage in Brazil, a complex phenomenon occurs from which vulnerabilities emerge: the approximation between housing and sewage treatment plants - ETE. To make matters worse, multicausality is not usually treated equally in quantitative environmental research - a fact that impacts more assertive decision-making. The objective is to analyze the socio-environmental vulnerabilities in the relationship between housing occupations and sewage treatment plant by stabilization ponds. A systemic methodology was adopted, by combining qualitative and quantitative methods. Empirical support was provided by ETE São Cristovão, located in a large outskirts of Fortaleza/CE/Brazil. The routine of technical procedures was composed as follows: bibliographic and documentary survey, on-site technical inspections, photographic images and georeferenced maps, calculation of the Water Quality Index (IQA), adoption of interviews and survey, application of Multiple Linear Regressions and Fuzzy Set QCA As a result, environmental vulnerability showed up in the constructive and operational failures of the ETE, in the bad IQA of the evaluated stretch and in the deficient environmental education of the population. Structural vulnerability resulted from poor road conditions and frequent flooding. Medium/high standard dwellings are also vulnerable if located in unhealthy. Social vulnerability was linked to family structure, resilience to environmental risks, the affective network, social belonging and time spent in residence - decisive variables to understand the context around the ETE. The regressions showed an inverse relationship between the proximity of the ETE and the feeling of environmental justice. The lived experiences were directly linked to environmental injustice and climate gentrification. The neighborhood's rating declined as the sense of environmental injustice increased. The Fuzzy Set QCA reported as configurations of perception of environmental injustice: absence of good environmental conditions or combination of presence of bad structural and social conditions. It was concluded that many problems were manifested in the environmental field. However, the feeling of environmental justice and housing dignity proved to be a driving force for the permanence of individuals in an unhealthy place. A more robust insertion of social parameters in the measurement of environmental indices is recommended, in order to provide greater precision in decisions and solutions involving equipment that promote pollution and insalubrity.